2011
DOI: 10.1016/j.chiabu.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Children exposed to child maltreatment and intimate partner violence: A study of co-occurrence among Hong Kong Chinese families

Abstract: The higher risk of child physical maltreatment associated with IPV highlights the need for an integrated assessment to screen for the presence of multiple forms of family violence within the family, and for intervention to assess effective responses to both IPV and child maltreatment by child protective service workers and domestic violence agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 65 publications
7
28
1
3
Order By: Relevance
“…To identify more of the children who would benefit from services, it is important that screening tools intended for children experiencing abuse or neglect also screen for IPV exposure (Chan 2011;Shen 2005). Furthermore, given that children's exposure to both physical and economic abuse was associated with negative outcomes, screening tools and interventions for child witnesses should account for multiple forms of violence, as well as the intensity of violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify more of the children who would benefit from services, it is important that screening tools intended for children experiencing abuse or neglect also screen for IPV exposure (Chan 2011;Shen 2005). Furthermore, given that children's exposure to both physical and economic abuse was associated with negative outcomes, screening tools and interventions for child witnesses should account for multiple forms of violence, as well as the intensity of violence.…”
Section: Discussionmentioning
confidence: 99%
“…It is unsurprising then, that childhood exposure to IPV and its effects on children's well-being and behavior should be an area of focus and concern. Child abuse, child neglect, and exposure to IPV exist across socioeconomic, educational, racial, and cultural lines (Pinheiro 2006;Chan 2011). In the U.S. alone, it is estimated that 15.5 million children reside in homes where they are exposed to some form of recurrent IPV (McDonald, Jouriles, Ramisetty-Mikler, Caetano, and Green 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to other works [12,55-57], all the issues associated with family environment and depression comprise an environment exposed to risk. Parental divorce, a bad relationship between father and child and violence are aspects that are causes of potential depression in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional family structure in India involves women moving after marriage to her husband’s community and co-residing with his parents and family. In this patrilocal cultural context, in-laws may be a source of protection or a source of violence and health risk for a woman [19, 20]. This may be independent of or in conjunction with violence and maltreatment from husbands; [19, 20] a recent study found that Indian women experiencing IPV during pregnancy or within 6 months postpartum were over five times more likely to report in-law violence (ILV) during this same period [21].…”
Section: Introductionmentioning
confidence: 99%